PERAN STRATEGIS RELAWAN PENDAMPING DALAM UPAYA PERLINDUNGAN PEREMPUAN DAN ANAK KORBAN KEKERASAN (Faculty of Social Science, Universitas Negeri Semarang, 2008)
Violence against women can happen anywhere and anyone perpetrators, regardless of their educationalstatus and social status. Perpetrators of sexual violence were close to the victims such as uncle, grandfather,teacher, neighbors, foster father and boyfriend. It took place in the victimâ€™s house, neighbors house,and public facilities such as toilets, public transportation like taxi, warehouses, gardens, schools anddormitories. Although the government has issued Law no. 23 23 Tahun 2004, about of Domestic Violence(PKDRT), in its implementation are still many obstacles. The lack of certainty of legal protection thatwill be fair for them to be the biggest obstacle in the process of selecting this litigation. The governmentshould took an active role in order to encourage women institution to be active in the community toprovide training, discussions and other activities that can â€œdismantleâ€ the understanding (perception) eachindividual will be the position of women in society, gender-based violence and the impact of violenceagainst women, improve the quality of life for the community.Keywords :Strategic role, voluntary assistance, domestic violance